1991
DOI: 10.1002/jmv.1890340104
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐S1 and pre‐S2 gene‐encoded proteins in liver and serum in chronic hepatitis delta infection

Abstract: Frozen cryostat sections and sera from 30 patients with chronic delta infection were examined for pre-S1 and pre-S2 gene-encoded proteins, and the results were compared to markers in liver and serum HBV and HDV replication. Pre-S1 and pre-S2 were detected by indirect immunofluorescence (IF) in the liver in all 26 patients with histochemically demonstrable HBsAg. Pre-S peptides were found by double IF to have a predominantly cytoplasmic expression and to be located in the same hepatocytes expressing HBsAg. Live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…While L-HBsAg is not required for HDV assembly and release, it is essential for HDV infectivity [37]. However, the presence of pre-S proteins and HBsAg in the liver and serum does not indicate the replication of HBV, HDV, and secretion [22,46], suggesting that HDV replication occurs independently from HBV. The HDV genome does not encode its own polymerase but utilizes the host RNA polymerase II the viral replication, while HBV has its own viral polymerase that can be targeted by specific inhibitors [47].…”
Section: Structure and Genome Organizationmentioning
confidence: 99%
“…While L-HBsAg is not required for HDV assembly and release, it is essential for HDV infectivity [37]. However, the presence of pre-S proteins and HBsAg in the liver and serum does not indicate the replication of HBV, HDV, and secretion [22,46], suggesting that HDV replication occurs independently from HBV. The HDV genome does not encode its own polymerase but utilizes the host RNA polymerase II the viral replication, while HBV has its own viral polymerase that can be targeted by specific inhibitors [47].…”
Section: Structure and Genome Organizationmentioning
confidence: 99%
“…Transfection experiments have shown that HDV can replicate within infected cells without helper virus [5,6,27], and that the helper function of HBV is to provide the envelope proteins in HDV virion assembly [28]. Recent data indicate that in the acquisition by repli- 12 Napoli/Fiorc/Fcra/Modugno/Giannelli/ Manghisi/Schiraldi eating HDV of an HBV-derived envelope in the liver, both HBsAg and preS proteins are concomitantly avail able [8]. Further investigations are necessary to establish whether the preSl and preS2 proteins are involved in the spread of HDV.…”
Section: Discussionmentioning
confidence: 99%
“…By using Western blot technique, Theilmann et al [7] have found that only 12% of HBsAg-positive anti-HD-positive patients had preSl proteins in the serum; more recently, preSl and preS2 peptides, detected by means of an immunoenzymatic reaction, have been found in 80 and 90% of patients with chronic HDV infec tion, respectively [8],…”
mentioning
confidence: 99%